Pengaruh Lingkungan, Motivasi, Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) Kabupaten Gorontalo - Trias Gani; Yakup Yakup; Hasanuddin Hasanuddin (Jurnal Simki Economic, 2025)
This study explores how environmental factors, motivation, and work discipline affect staff performance at the Public Works and Spatial Planning (PUPR) Office of Gorontalo Regency. Human resources are a crucial element in an organization, and employee performance is influenced by a number of factors both internal and external. The purpose of this study is to analyze the impact of these three factors on employee performance. The method used in this study is a quantitative approach, by distributing questionnaires to 44 staff at PUPR Gorontalo Regency. The collected data were then analyzed using multiple linear regression. The findings of this study reveal that the environment, motivation, and work discipline have a significant positive impact on employee performance. These results emphasize the importance of creating a supportive work atmosphere, increasing motivation, and maintaining work discipline in order to increase organizational productivity.